(untitled) (Annals of Medical Research, 2024)
Aim: Atrial fibrillation (AF) recurrence occurs in 20-30% of patients despite cryoablation treatment. We aimed to investigate the importance of CHA2DS2-VASc, TIMI-AF, ATRIA, HASBLED and EHRA scoring systems in identifying patients with late-stage AF recurrence in patients who received cryoablation due to paroxysmal AF (PAF). Materials and Methods: This cross-sectional study included 300 patients who received cryoablation because of PAF. EHRA, CHA2DS2-VASc, TIMI AF, ATRIA and HASBLED scores used in the clinic were calculated for AF burden, stroke and bleeding risk in patients. AF recurrence was defined as detection of AF in 12-lead electrocardiography or observation of AF attack for at least 30 seconds in Holter ECG recording. Patients were divided into 2 groups as patients with and without AF recurrence. Results: In the follow-up of patients who underwent cryoablation due to PAF, AF recurrence was detected in 47 (16%) patients. CHA2DS2-VASc, ATRIA, HASBLED and EHRA scores were significantly higher in the patient group with AF recurrence (p<0.05 for each). TIMI-AF score was similar between the two groups. When logistic regression analysis was performed to identify patients with AF recurrence, variables of HT (OR:3.322, 95% CI:1.659 – 6.620, p=0.001), BMI (OR:1.087, 95% CI:1.011 – 1.169, p=0.024) and EHRA scoring system (OR:3.503, 95% CI:1.680 – 7.306, p=0.001) were determined as independent markers for AF recurrence. Conclusion: The results of our study showed that EHRA scoring system should be used for AF ablation decision, as well as its ability to predict AF recurrence, would be clinically useful.